Traitement de l'hemangiome du gland par laser Nd : Yag - Amaro, J. L. [UNESP]; Agostinho, A. D. [UNESP]; Polido, A. [UNESP]; Costa, R. P. [UNESP]; Trindade Filho, J. C.S. [UNESP]; Trindade, J. C.S. [UNESP] (My University, 1997)
Hemangioma of urinary tract are anusual, being about 2% of all hemangiomas. We present a case of a glans penis hemangioma. There is controversy concerning their treatment and outcome. Our patient was treated with a Neodymium: Yag laser irradiation, with complete morphological recuperation.
Nd-Yag laser treatment of glans penis hemangioma. Case report
Keywords: Glans penis; Hemangioma; Nd-Yag laser treatment